A phase 1 study of the c‐Met inhibitor, tivantinib (ARQ197) in children with relapsed or refractory solid tumors: A Children's Oncology Group study phase 1 and pilot consortium trial (ADVL1111). Issue 11 (27th April 2017) - Geller, James I.; Perentesis, John P.; Liu, Xiaowei; Minard, Charles G.; Kudgus, Rachel A.; Reid, Joel M.; Fox, Elizabeth; Blaney, Susan M.; Weigel, Brenda J.
Abstract: Background: The c‐Met receptor tyrosine kinase is dysregulated in many pediatric cancers. Tivantinib is an oral small molecule that inhibits the c‐Met receptor tyrosine kinase. A phase 1 and pharmacokinetic (PK) trial evaluating tivantinib was conducted in children with relapsed/refractory solid tumors. Methods: Oral tivantinib capsules were administered twice daily with food, continuously in 28‐day cycles. Dose levels 170, 200, and 240 mg/m 2 /dose were evaluated using a rolling‐six design (Part A). In Part B, subjects received tivantinib powder sprinkled on food at the recommended phase 2 dose (RP2D) from Part A. PK, CYP2C19 genotyping, and baseline tumor tissue c‐Met expression were analyzed. Results: Thirty‐six patients were enrolled: 20 in Part A, 6 in a PK expansion cohort, and 10 in Part B. Fifteen patients had primary central nervous system tumors and 21 had solid tumors. In Part A, there were no dose‐limiting toxicities. One grade 4 intracranial hemorrhage occurred in a patient with a progressive brain tumor in the expanded PK cohort (240 mg/m 2 ). PK analysis showed marked interpatient variability (20‐fold) in the Cmax and AUC0‐8h across all dose levels. Sprinkling tivantinib powder over food did not alter exposure. Membranous and total c‐Met expression was moderate (2), low (4), or not detected (26). Two patients had stable disease as the best response. Conclusions: The RP2D of tivantinib given with food in children with refractory solid tumors is 240 mg/m 2 /dose. PK of tivantinib in children demonstrated high variability. Objective responses were not observed in this phase 1 trial.